Analysis of Comparative Fixation Time in Quality Control of Breast FNAB Preparations with Quick Diff Staining - Indra Sabban; Rizal Hermawan; Ismiy Wahyuni; Nawang Ilmiafee; Ambar Ningtyas (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2023)
The breast is a body part consisting of fatty tissue, fibrous glands, and connective tissue that is connected to the muscles of the chest wall. In the physiological processes of the body, there are several factors in breast cells that experience abnormal development which causes breast lumps. The prevalence of breast cancer in Indonesia is 65,858 (Globocan, 2020). At the Nganjuk Regional Hospital in 2022, 71 patients were examined for FNAB breasts from June to November. The cytological diagnosis performed was FNAB examination using the diff quick staining method with dry fixation. This research aims to determine the comparative analysis of fixation time on the quality control of breast FNAB preparations with diff quick staining at Nganjuk Regional Hospital. The research design uses an experimental method that tests between two variables and a comparative research, which compares the factors that influence research from different experimental designs. The population of this research were outpatients and inpatients of breast FNAB at the Nganjuk Regional Hospital by Quota Sampling method. Based on the Friedman statistical test, it can be concluded that there are differences in color quality control of breast FNAB preparations using diff quick staining with fixation time.